Faculty of Computing will be operating in UMP Pekan in October - Nor Salwana, Mohammad Idris (2020)
Pekan, 13 July 2020 - Faculty of Computing (FK), Universiti Malaysia Pahang (UMP) which has more than 1,500 undergraduate and postgraduate students will operate and start teaching and learning sessions in a new building located at UMP Pekan starting next October.